Dual targeting: Combining costimulation blockade and bortezomib to permit kidney transplantation in sensitized recipients. Issue 3 (17th September 2018) - Burghuber, Christopher K.; Manook, Miriam; Ezekian, Brian; Gibby, Adriana C.; Leopardi, Frank V.; Song, Minqing; Jenks, Jennifer; Saccoccio, Frances; Permar, Sallie; Farris, Alton B.; Iwakoshi, Neal N.; Kwun, Jean; et al.
Abstract : Previous evidence suggests that a homeostatic germinal center (GC) response may limit bortezomib desensitization therapy. We evaluated the combination of costimulation blockade with bortezomib in a sensitized non‐human primate kidney transplant model. Sensitized animals were treated with bortezomib, belatacept, and anti‐CD40 mAb twice weekly for a month (n = 6) and compared to control animals (n = 7). Desensitization therapy–mediated DSA reductions approached statistical significance ( P = .07) and significantly diminished bone marrow PCs, lymph node follicular helper T cells, and memory B cell proliferation. Graft survival was prolonged in the desensitization group ( P = .073). All control animals (n = 6) experienced graft loss due to antibody‐mediated rejection (AMR) after kidney transplantation, compared to one desensitized animal (1/5). Overall, histological AMR scores were significantly lower in the treatment group (n = 5) compared to control ( P = .020). However, CMV disease was common in the desensitized group (3/5). Desensitized animals were sacrificed after long‐term follow‐up with functioning grafts. Dual targeting of both plasma cells and upstream GC responses successfully prolongs graft survival in a sensitized NHP model despite significant infectious complications and drug toxicity. Further work is planned to dissect underlying mechanisms, and explore safety concerns. Abstract : Targeting both plasma cells and the germinal center response with proteasome inhibition and costimulation blockade successfully desensitizes and prolongs renal allograft survival in a highly sensitized nonhuman primate model despite significant infectious complications and drug toxicity.